2020
DOI: 10.1002/anie.201915075
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Sequence Control and Sequence‐Driven Properties in a Series of AB‐Alternating Copolymers Consisting Solely of Acrylamide Units

Abstract: Herein, we report a method to synthesize a series of alternating copolymers that consist exclusively of acrylamide units. Crucial to realizing this polymer synthesis is the design of a divinyl monomer that contains acrylate and acrylamide moieties connected by two activated ester bonds. This design, which is based on the reactivity ratio of the embedded vinyl groups, allows a “selective” cyclopolymerization, wherein the intramolecular and intermolecular propagation are repeated alternately under dilute conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 46 publications
(5 reference statements)
4
42
0
Order By: Relevance
“…This is likely due to the heterogeneity of the monomer composition in the copolymers, arisen from the conventional free radical polymerization method. The NtBAM content is an average value, and the sample is constituted of a mixture of statistical copolymers with NtBAM-richer and NIPAM-richer rather than the average value compositions [22,30]. The cloud point temperature (T cp ) was defined as the temperature where the optical density of the studied polymer solution increases promptly.…”
Section: Synthesis and Characterization Of Graft Copolymersmentioning
confidence: 99%
“…This is likely due to the heterogeneity of the monomer composition in the copolymers, arisen from the conventional free radical polymerization method. The NtBAM content is an average value, and the sample is constituted of a mixture of statistical copolymers with NtBAM-richer and NIPAM-richer rather than the average value compositions [22,30]. The cloud point temperature (T cp ) was defined as the temperature where the optical density of the studied polymer solution increases promptly.…”
Section: Synthesis and Characterization Of Graft Copolymersmentioning
confidence: 99%
“…that are far superior to the corresponding copolymers with random monomer sequences. [8,[14][15][16][17][18][19][20][21][22][23] It has been demonstrated that the copolymers of poly(lactide-co-glycolic acid) with unique sequences of lactide and glycolic acid possess specific hydrolysis patterns and degradation rates. [4,[24][25] Furthermore, precisely positioned reactive functional monomers in the polymer chain could allow generation of folded polymers to prepare diverse macromolecular origamis or polymer nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–13 ] Comparing with the copolymer with random structure, the alternating copolymer showed more sensitivity in response to the thermal stimulation. [ 14,15 ] Though promising, the low selectivity of the comonomer addition during chain growth hindered the sequence control over the polymerization, especially for chain growth mechanism. [ 16–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] For example, Sawamoto et al. developed concurrent tandem catalysis‐based methodology, [ 25–28 ] template‐initiator, [ 29,30 ] template‐monomer strategies [ 14,15,31–34 ] for generating the sequence‐controlled polymers. Kamigaito et al.…”
Section: Introductionmentioning
confidence: 99%